Konsep Meminta Maaf Sebagai Hukuman Dalam Perkara Pidana - Yusi Amdani; Liza Agnesta Krisna (Fakultas Hukum Universitas Islam Indonesia, 2019)
Criminalization is an act against a criminal, but many criminal cases are completed as a result of theimplementation of peace by apologizing. This research focuses on the following problems: first, how the reconceptualization of apologizing as the part of the punishment is reviewed in accordance with the positive law and Islamic law, and second, how the realization of the concept of apoligizing as a punishment in a criminal case is. The research method used in this study is normative juridical. From the results of the study, it can be concluded that, first, the concept of apologizing is known in criminal law and Islamic law. Regarding the virtue of Islamic law, the concept of apologizing is able to eliminate the criminal acts; thus, the value of the apologizing concept in Islamic law can be applied in criminal law. In national criminal law, the concept of apologizing is implicitly accommodated in the peace process, which in certain criminal acts, especially in the category of minor criminal offenses, is permitted to make peace. Second, some cases that can be given peace are also determined for certain cases such as accidents in traffic, crimes committed by underage child, and other acts constituting the minor crimes by the category of complaint offenses.